The impact of debt finance on the financial performance of a small to medium entity: a case of Workman Zimbabwe (Private) Limited - Koshita, Ruth N. (Midlands State University, 2020)
The main purpose of this research was to determine the impact of debt finance on a small to medium entity, a case of Workman Zimbabwe (Private) Limited. The management reports of the company showed a recurring decline in profits, increase in interest costs as well as high gearing ratios from 2015 to 2017. This had resulted in greater variances between budgeted amounts and actual amounts raising a cause for concern thereby necessitating the need for this research. Literature from various researchers was outlined to obtain different views on theories on debt finance, impact of debt on financial performance, other possible causes of poor financial performance and measures to improve financial performance. Primary data was collected through interviews and questionnaires. Secondary data was obtained from company management accounts. Data presentation and analysis was done on the objectives of the study and regression analysis was used to analyse data. The researcher concluded that debt has a significant influence on the financial performance of Workman Zimbabwe with short term debt having a significant negative effect whilst long term debt has a negative effect on financial performance.